ECONOMIC VALUATION MODEL OF VANNAME SHRIMP CULTURE AND MANGROVE REHABILITATION - Mongi, Elrin Meivian Mongi; Karuniasa, Mahawan; Patria, Mufti Petala (UI Scholars Hub, 2023)
The current climate change is caused by anthropogenic activities involving energy and industry usage that affect the temperature and climate of the Earth. The Paris Agreement on climate change is a commitment by some countries to act to address climate change by developing sustainably and emitting low levels of carbon dioxide (CO2). Changes in the oceans include temperature increases, acidification, and changes in currents, leading to decreased productivity in fishing and aquaculture. Integrated mangrove shrimp farming, known as silvofisheries, has been recognized as environmentally friendly cultivation. The implementation of silvofishery is a form of mangrove ecosystem management that integrates ecology and economics. An economic and ecological valuation is needed in the Vannamei shrimp farming business. Therefore, this study aims to build an economic model of mangroves and shrimp farming. The data were analyzed and simulated using Systems Dynamic. Based on Business as Usual (BAU) simulation predictions for the 2023 mangrove area of 267 hectares, the best scenario for the mangrove area of 2033 is 1,770 hectares, the total economic value of shrimp of Rp 49,300,000,000 and the total economic value of mangrove is Rp 77,175,000,000. This research results in a potential trade-off between intensive shrimp farming businesses and mangrove rehabilitation to maintain a business's sustainability and the environment's carrying capacity.